Deliberative Collaborative Governance Approaches to Sustainability Assessment - Petrova, Svetla; Hartz-Karp, J.; Pope, J. (2015)
The Handbook of Sustainability Assessment introduces the theory and practice of sustainability assessment and showcases the state-of-the-art research.